CAN DEVELOPMENT BE MEASURED? BEYOND INDICATORS AND GIS: ASSESSING THE REAL IMPACTS OF THE HUNGARY–CROATIA INTERREG PROGRAMME - RAVLIĆ, SANELA (Economic Outlook, 2026)
: This paper examines the extent to which the real impacts of cross-border cooperation programmes can be adequately measured using conventional evaluation indicators. Using the Hungary–Croatia INTERREG Programme as a case study, the research aims to analyse whether existing monitoring and evaluation systems capture actual developmental changes within border communities. The study is based on the assumption that administratively measurable indicators do not necessarily reflect the broader social, institutional, and developmental impacts of cooperation programmes. The research applies a qualitative analysis of scientific literature, programme evaluation reports, previous empirical studies, and GIS-based territorial analysis. The findings indicate that while existing evaluation systems successfully measure programme outputs and financial performance, they only partially capture intangible effects such as knowledge transfer, social capital development, institutional networking, and the sustainability of cooperation. The paper concludes that a more comprehensive evaluation framework combining quantitative indicators, qualitative evidence, and territorial analysis is needed to assess the real impacts of cross-border cooperation.
Keywords: cross-border cooperation, INTERREG, programme evaluation, territorial development, GIS.